RUSSIAN LANGUAGE IN MEDIA AND POP CULTURE: INFLUENCE AND DEVELOPMENT - Sultanmuradova Farangiz Akramovna; Ismatillayeva Charos Olimjonovna; Ochilova Dilrabo Odilovna (European Science Publishing, 2024)
The Russian language occupies a significant place in the media and pop culture, influencing the formation of public opinion, cultural identities and social discourses. In the field of media, it serves as the main means of communication, ensuring the wide dissemination of information through television, print media and digital platforms. In pop culture, the Russian language is manifested in music, literature and cinema, reflecting modern trends and problems of society. The article examines the role of the Russian language in these spheres, emphasizing its influence and the challenges it faces in the context of globalization and the dominance of the English language.
Keywords: russian language, mass media, pop culture, television, print media, digital media, music, literature, cinema, globalization.